Design of a Simplified Experimental Test Case to Study Rotor–Stator Interactions in Hydraulic Machinery - Dussault, Benoit; St-Amant, Yves; Houde, Sébastien (Energies (Basel), 2025)
Because of the introduction of significant amounts of electricity from intermittent energy, such as solar and wind, on power grids, hydraulic turbines undergo more transient operation with varying rotation speeds. Start and stop sequences are known to induce significant mechanical stress in the runner, decreasing its lifespan. Complex fluid–structure interactions are responsible for those high-stress levels, but the precise mechanisms are still elusive, even if many experimental and numerical studies were devoted to the subject. One possible mechanism identified through limited measurements on large turbines operating in powerhouses is rotor–stator interactions. It is already known that rotor–stator interaction (RSI) in constant-speed operating conditions can lead to runner failure when the RSI frequency is close to the natural frequencies of specific structural modes. Start and stop sequence investigations show that RSI can induce a transient resonance while the runner is accelerating/decelerating, which generates a frequency sweep that excites the structure. Studying transient RSI-induced resonance of structural modes associated with hydraulic turbine runners is complex because of the geometry and the potential impacts from other flow-induced excitations. This paper presents the development and validation of an experimental setup specifically designed to reproduce RSI-induced resonances in a rotating circular structure with cyclic periodicity mimicking the structural behavior of a Francis runner. Such a setup does not exist in the literature and will be beneficial for studying RSI during speed variations, with the potential to provide valuable insights into the dynamic behavior of turbines during transient conditions. The paper outlines the different design steps and the construction and validation of the experiment and its simplified runner. It presents important results from preliminary analyses that outline the approach’s success in investigating transient RSI in hydraulic turbines.